2012
DOI: 10.1063/1.3689553
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of stable high-temperature Dx-CO intermediates on the Ru(0001) surface

Abstract: We demonstrate the formation of complexes involving attractive interactions between D and CO on Ru(0001) that are stable at significantly higher temperatures than have previously been reported for such intermediate species on this surface. These complexes are evident by the appearance of new desorption features upon heating of the sample. They decompose in stages as the sample temperature is increased, with the most stable component desorbing at >500 K. The D:CO ratio remaining on the surface during the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Upon deposition at 77 K, largely disordered structures are observed, while subsequent annealing to temperatures between 150 and 225 K results in small triangular islands containing from 3 to 21 CO molecules in close proximity, stabilized by a surrounding (1 × 1)-H background. In agreement with previous TPD investigations of coadsorbed CO and H (D), we found that further annealing to 300–350 K results in hydrogen desorption , and CO rearranging into periodic structures of roughly hexagonal 7CO or 19CO units …”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Upon deposition at 77 K, largely disordered structures are observed, while subsequent annealing to temperatures between 150 and 225 K results in small triangular islands containing from 3 to 21 CO molecules in close proximity, stabilized by a surrounding (1 × 1)-H background. In agreement with previous TPD investigations of coadsorbed CO and H (D), we found that further annealing to 300–350 K results in hydrogen desorption , and CO rearranging into periodic structures of roughly hexagonal 7CO or 19CO units …”
Section: Introductionsupporting
confidence: 92%
“…Using helium atom scattering (HAS), they deduced an average “magic” size of seven CO molecules per island . Similarly, TPD experiments using molecular beams to dose D 2 onto a CO-precovered surface showed the formation of complexes with a CO to deuterium (D) ratio of 1:1, involving attractive interactions between the two species on Ru(0001) . Another TPD study was reported for CO and H coadsorption on a Pt/Ru surface alloy, combined with infrared reflection absorption spectroscopy (IRAS), suggesting that the total coverage of adsorbed H and CO is higher than the sum of the saturation coverages of both molecules, again indicating attractive interactions between the two species. , These different findings indicate that the interaction potential between CO and H on a Ru surface is highly complex.…”
Section: Introductionmentioning
confidence: 98%
“…In the presence of hydrogen, the coupling of hydrogen with CO, followed by C-O bond cleavage is found on Ru(0001) surface, which lowers the C-O fragmentation barrier [7][8][9][10]. The hydrogenation process on surfaces, which is responsible for the enhanced interaction with the surface, is predicted to be important for this hydrogen-assisted dissociation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Before turning to the results of this study, we will briefly summarize previous findings on the coadsorption of CO and hydrogen on Ru(0001) and Pt(111) surfaces and on monolayer PtRu/Ru(0001) surface alloys as reference. The coadsorption of CO and hydrogen (deuterium) on Ru(0001) has been the subject of several experimental and theoretical studies. TPD experiments by Peebles et al demonstrated that neither preadsorbed CO ad nor D ad species are displaced by exposure to the respective other species at 100 K. Shifts of the thermal desorption states in D 2 TPD spectra to lower temperatures indicated a repulsive interaction between the coadsorbed species CO ad and D ad . This observation was supported by Mak et al, who explained a decrease of the H ad diffusion coefficient with increasing CO coverage in coadsorbed layers by repulsive adsorbate–adsorbate interactions and formation of segregated islands of the coadsorbed species.…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular beam experiments by Ueta et al found evidence for the formation of stabilized D x −CO y species on the surface for medium CO ad precoverages and higher D 2 beam energies. 21 For coadsorption of CO and hydrogen on Pt(111), an early study by Baldwin indicated that it is possible to form a CO−H adsorption complex on the surface. 25 Later studies, however, concluded that the two adsorbate species form segregated islands on Pt(111) as a consequence of repulsive adsorbate− adsorbate interactions between CO ad and H ad .…”
Section: Introductionmentioning
confidence: 99%